2017
DOI: 10.1210/en.2016-1898
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenemia Induced by Letrozole Treatment of Pubertal Female Mice Results in Hyperinsulinemia Prior to Weight Gain and Insulin Resistance

Abstract: Women with polycystic ovary syndrome (PCOS) diagnosed with hyperandrogenism and ovulatory dysfunction have an increased risk of developing metabolic disorders, including type 2 diabetes and cardiovascular disease. We previously developed a model that uses letrozole to elevate endogenous testosterone levels in female mice. This model has hallmarks of PCOS, including hyperandrogenism, anovulation, and polycystic ovaries, as well as increased abdominal adiposity and glucose intolerance. In the current study, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 94 publications
13
29
0
1
Order By: Relevance
“…As reported in previous studies (27, 29, 30), five weeks of letrozole treatment resulted in increased FBG and insulin levels and insulin resistance (Fig. 1D-F).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…As reported in previous studies (27, 29, 30), five weeks of letrozole treatment resulted in increased FBG and insulin levels and insulin resistance (Fig. 1D-F).…”
Section: Resultssupporting
confidence: 87%
“…1B, weight was measured each week during the 5 weeks of treatment. Similarly to previously published studies (27, 30), 2 weeks of letrozole treatment resulted in increased weight compared to placebo treatment that was maintained for the rest of the study (Fig. 1B).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Letrozole treatment resulted in many reproductive hallmarks of PCOS including hyperandrogenism, acyclicity, polycystic ovaries, and elevated luteinizing hormone (LH) levels [26]. This model also exhibited metabolic dysregulation including weight gain, abdominal adiposity, increased fasting blood glucose (FBG) and insulin levels, and insulin resistance [27]. In addition, we demonstrated that changes in the gut microbiome were associated with letrozole treatment [28].…”
Section: Introductionmentioning
confidence: 83%